2015
DOI: 10.1007/s00256-015-2140-6
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor of soft tissue: a case report with emphasis on MR imaging

Abstract: Giant cell tumor of soft tissue is a rare neoplasm, histologically resembling giant cell tumor of bone. In this report, we describe a deep and solid giant cell tumor of soft tissue interpreted as a benign soft tissue tumor based on magnetic resonance (MR) findings with hypointense to intermediate signals on T2-weighted images and impeded diffusivity (water movement) on diffusion-weighted imaging (DWI), which could suggest a giant-cell-containing benign soft tissue tumor, despite the malignancy suggested by 18F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 12 publications
4
22
0
Order By: Relevance
“…After the pathological results came out, we analyzed the MRI images retrospectively, trying to find some imaging features that contribute to the diagnosis of this rare tumor. GCT-ST is a rare neoplasm, histologically resembling GCT of bone [810]. According to the histological features of GCT-ST [1113], the tumor shows multi-nodular structure under low power field, which varies in size and separated by fibrous connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…After the pathological results came out, we analyzed the MRI images retrospectively, trying to find some imaging features that contribute to the diagnosis of this rare tumor. GCT-ST is a rare neoplasm, histologically resembling GCT of bone [810]. According to the histological features of GCT-ST [1113], the tumor shows multi-nodular structure under low power field, which varies in size and separated by fibrous connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we used a conventional MRI and DWI approach to investigate two cases of soft tissue giant cell tumor in the limb. The radiologic abnormalities of all lesions were limited to soft tissue without obvious calcification or bone erosion, which are frequently observed at the periphery of the GCT-ST tumors [2][3][4][5][6][7] . In addition, all lesions on MRI presented with solid masses, and blurry boundaries on the upper and lower edges.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, all lesions were significantly big (maximum lesion size ranged from 4.0 cm to 6.0cm) and were located in the superficial areas of extremities or trunk. This type of lesion is commonly observed in GCT-ST, but it can also be found in the deep soft tissues of head, neck and retroperitomeum region [2][3][4][5][6][7][8][9][10] . Unlike deep-seated masses, size criteria (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologically, GCT-ST lesions bear a close resemblance to their bony counterparts, giant cell tumor of bone. Most of the existing reports are pathological and clinical studies, while the imaging aspects have only been reported in the cases of adjacent bone or with atypical cystic degeneration [2][3][4][5][6][7][8][9][10][11] . With regard to MR or ultrasonography imaging features, superficial masses can be further identified based on facial edema, skin thickening, skin contact, internal hemorrhage or necrosis and lobulation of the mass [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%